2014
DOI: 10.1080/14926156.2014.935526
|View full text |Cite
|
Sign up to set email alerts
|

Recovering Knowledge for Science Education Research: Exploring the “Icarus Effect” in Student Work

Abstract: Science education research has built a strong body of work on students' understandings but largely overlooked the nature of science knowledge itself. Legitimation Code Theory (LCT), a rapidly growing approach to education, offers a way of analyzing the organizing principles of knowledge practices and their effects on science education. This article focuses on one specific concept from LCT-semantic gravity-that conceptualizes differences in context dependence. The article uses this concept to qualitatively anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 27 publications
2
24
0
9
Order By: Relevance
“…The temperature decrease is caused primarily by the phase change from liquid to gas state in the container as gas is released, during which energy is required to break bonds in the liquid CO 2 . In our experience, however, in line with Georgiou et al, 18 students often fail to recognise the centrality of the phase change in the process. It should be noted here that the types of handheld IR cameras we used detect radiation primarily from solid and liquid surfaces, but not from gases, due to their low density.…”
Section: Cooling Through Joule-thomson Throttlingmentioning
confidence: 48%
“…The temperature decrease is caused primarily by the phase change from liquid to gas state in the container as gas is released, during which energy is required to break bonds in the liquid CO 2 . In our experience, however, in line with Georgiou et al, 18 students often fail to recognise the centrality of the phase change in the process. It should be noted here that the types of handheld IR cameras we used detect radiation primarily from solid and liquid surfaces, but not from gases, due to their low density.…”
Section: Cooling Through Joule-thomson Throttlingmentioning
confidence: 48%
“…Making these characteristics explicit then allows better understanding of the use of technology in these classrooms. In terms of student understanding, Georgiou et al, [30] found that this was facilitated by identifying and characterising a particular element of knowledge, its abstraction. The research demonstrated that there was an underlying code in terms of abstraction when students answered typical exam-style questions: abstract, but not too abstract (e.g., the referring to the energy of phase change, rather than the employment of the ideal gas law).…”
Section: Introductionmentioning
confidence: 99%
“…An external language of description was created, using the study reported in Georgiou, Maton, and Sharma (2014) as a model, to analyze the degrees of semantic gravity in the text "Solar Storm," as shown in Figure 2.…”
Section: The External Language Of Descriptionmentioning
confidence: 99%